Analysis of distribution patterns and marketing margins of capture fishery products at the Ujong Baroh fishing port, West Aceh district, Indonesia. Issue 1 (November 2021) - Perdana, A W; Affan, J M; Hasri, Q; Miswar, E; 'Akla, C M N; Batubara, A S
Abstract: The objectives to be achieved in this study are to determine the distribution pattern of capture fishery products at Ujong Baroh Fishing Port and determine an efficient distribution pattern in conducting a marketing system by knowing the margin received. The method used in this study is a survey method with purposive sampling data collection techniques. The data analysis used in this research is descriptive analysis and marketing margin analysis. The descriptive analysis used to describe the distribution pattern in Ujong Baroh Fishing Port. Marketing margin analysis is used to measure the profits of each actor involved in the catch distribution pattern. Results of this study obtained 2 distribution patterns that occur in Ujong Baroh Fishing Port. The first distribution pattern is fishermen to fish collectors to wholesalers to retailers to consumers; second, fishermen to fish collectors to traders to consumers. Both distribution patterns at Ujong Baroh Fishing Port are correct because these patterns get a marketing margin value of < 50% and a fisherman's profit sharing value of > 50%, where the distribution pattern is classified as efficient. The party who benefits from both distribution patterns is fish collectors because they get a sales profit of 7%.